Profit inefficiency of goat farming in Malawi: A Bayesian approach - Chifundo Nyakwawa; Assa Mulagha-Maganga; Julius H. Mangisoni (Heliyon, 2022)
Goat farms located in villages constitute an important sub-sector to buffer household livelihoods against climate shocks in absence of insurance markets, and thus the need to intensify production to meet the growing goat meat demand. There has been little attempt to quantify the efficiency of goat farms and the associated drivers. Potential initiatives to bolster goat farm incomes have not gone beyond production. Using the Bayesian Stochastic Frontier Approach and Malawi's national Integrated Household Panel Survey data from 2010 to 2019, we analyze the profit efficiency of goat farming and the priority drivers that influence inefficiencies across production plants. The findings reveal that farmers are operating below the profit frontier and 71% of the profit-loss is influenced by farm characteristics. The results further suggest that policies involving stirring commercializing and specialization are key to closing the efficiency gap. Finally, the study proposes new policy directions, namely, government provision of livestock extension services to farmers, incorporating goat farming into women's empowerment programs, and provision of access to tailor-made livestock microfinance loans.